Treatment outcome of the retreatment tuberculosis patients under RNTCP in eastern Uttar Pradesh - Gautam, Praveen B.; Mishra, Ashwini Kumar; Kumar, Santosh (International Journal Of Community Medicine And Public Health, 2017)
Background: India has the highest tuberculosis (TB) burden in the world. The directly observed treatment strategy is the most systemic and cost-effective approach to the disease. Furthermore, understanding the reasons for treatment outcome is important for the improvement of treatment systems. The objective was to study the treatment outcome of retreatment tuberculosis patients under RNTCP in eastern UP. Methods: A longitudinal cohort study was undertaken among total 205 patients registered in category II under DOTS from June 2015 to May 2016. These patients were followed up to November 2016 till the completion of treatment. At the end of study period, treatment outcomes were analysed. The chi-square test was used to assess the statistical significance of each ratio. P<0.05 was considered significant. Results: Out of 205 re-treatment patients, 174 (84.4%) had pulmonary tuberculosis while 31 (15.1%) had extra-pulmonary TB. In the cohort of category II patients 93 (45.3%) were relapse, 58 (28.2%) belonged to others category, 31 (15.1%) were treatment after loss to follow-up and 23 (11.2%) were on treatment after failure. Maximum patients were male 133 (64.8%) and most of the patients were belonged to the age group of 20-40 years. Among retreatment cases the cure rate for relapse, treatment after failure, treatment after loss to follow-up and others cases were 74.1%, 60.8%, 35.4% and 55.1% respectively. Conclusions: The relapse cases were the most commonly found in the re-treatment category however these patients were more likely to be cured with the category II regimen and treatment after loss to follow-up had high risk of retreatment failure. Continuous monitoring, adherence and treatment completion are essential for controlling the need of retreatment as well as improvement of tuberculosis control programme.